FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KONSUMSI PANGAN SUMBER KARBOHIDRAT DI PERDESAAN DAN PERKOTAAN - Suci Apriani; Yayuk Farida Baliwati (Food and Nutrition Society of Indonesia, 2011)
The aims of study were to analyze the ecological factors such as food availability, land capacity, population density, poverty, GDP, education; and their association to the consumption of carbohydrate food sources in some rural and urban areas of Indonesia. This ecological study was conducted by analysing the 62 districts in Indonesia. The data of food consumption was part of set Riset Kesehatan Dasar (Riskesdas 2007). The data of food production, population density, poverty, GDP, and education collected from the Central Statistic Agency (BPS). The statistical test was pearson correlation and stepwise linear regression. The study shows that consumption of carbohydrate food sources in rural more than in urban area and dominated by rice. Energy contribution from carbohydrate food sources is a half of total energy contribution (55.9% in rural and 48.05% in urban). In rural area, consumption of rice, corn, cassava, and sweet potato per capita per year were 109 kg, 4.69 kg, 2.51 kg, and 0.66 kg. While in urban area, consumption of rice, corn, cassava, and sweet potato per capita per year were 95 kg, 1.24 kg, 3.51 kg, and 0.209 kg. The food availability was significantly affected to the consumption of carbohydrate food sources in rural and urban areas.